The influence of meaningful work on the mental health of SME employees in the COVID-19 era: can coping strategies mediate the relationship? - Muhammad Farhan, Jalil; Azlan, Ali (BioMed Central, 2023)
Background Stress, depression, and anxiety are prevalent issues among SME employees during the COVID-19 pandemic. Even while having meaningful work that expressively contributes to individual growth has been related to improving mental health, employees’ work may also need to adopt coping strategies to increase outcomes. The purpose of this study was to examine the relationship between meaningful work (positive meaning, meaning-making, and greater good motivations) and mental health, as well as coping strategies (problem-focused and emotion-focused) as a mediator of this relationship.